PTU-140 Intrahepatic Tregs Are Plastic But Functional And Biliary Epithelial Cells Support Their Fate. (9th June 2014) - Chen, Y-Y; Hannah, J; Birtwistle, J; Novitzky Basso, I; Lalor, P; Adams, DH; Oo, YH
Abstract : Introduction: Regulatory T cells (Tregs ) are crucial in maintaining peripheral tolerance. Tregs control T effector CD8, CD4, Th1 cells along with other immune cells to maintain hepatic tolerance. They are implicated in both human and murine model of hepatic inflammation including autoimmune hepatitis, viral hepatitis, liver cancer and post-transplantation tolerance. However little is known about the lineage stability, function and fate of human intrahepatic Tregs in the inflamed microenvironment. Methods: Human liver infiltrating (LI) lymphocytes were freshly isolated from explanted liver tissues. LITregs cells surface phenotype, chemokine and cytokine receptor expression, intracellular-cytokine secretion was assessed ex-vivo by flow cytometry. Function and plasticity of post-endothelial transmigrated (PEM) Tregs in the inflamed microenvironment was assessed by suppression assays and flow cytometry. Distribution and localisation of LITregs in tissue was determined using dual immunohistochemistry and confocal microscopy. Cytokine expressions by the liver microenvironment were studied in vitro using Luminx. Real time PCR was used to study the mRNA expression. Survival and proliferation of PEM Tregs in microenvironment was studied in-vitro using co-culture assays using primary human biliary epithelial cells. Results: LITregs highly express CD39 (57 ± 11%), CD95 (83 ± 4%), CD27 (73 ± 3%), CD44 (90 ± 3%) and low expression of CD40 (6.813 ± 3.25%). Cytokine receptors expression was (31 ± 15%) for IL15R, (17 ± 15%) for IL6R-α. Hepatic microenvironment is highly enriched with IL-1β (363 ± 88 pg/ml), IL-6 (8, 960±pg/ml), IL-12 (44 ± 35 pg/ml), IFN-γ (21 ± 8.33 pg/ml). Minimal level of IL-2 was detected in inflamed liver supernatant. Post-endothelial migrated (PEM) Tregs and Tregs in the inflamed microenvironment are functional but suppression capacity was reduced in Tregs residing in the inflamed liver. Plasticity to other T cells lineage is minimal for Tregs in the inflamed microenvironment. LITregs reside close to bile ducts at the portal tract. Co-culture experiment of PEM Tregs and with biliary epithelial cells suggested that Tregs survival depends on FAS-FASL pathway and IL-2. Conclusion: LITregs are plastic but functional in the inflamed intrahepatic microenvironment and their fate around biliary epithelial cells is supported via IL-2 cytokine and CD95-CD95 ligand pathway. Disclosure of Interest: None Declared.